Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas VIII SMP - Marbun, Four Marito (Unika Santo Thomas Medan, 2019)
The purpose of this study was to determine the effect of the cooperative Student Teams Achievement Devision (STAD) learning model on the ability to understand students 'mathematical concepts and students' responses to the STAD cooperative learning model type. This research method is a quasi experimental method. This research was conducted in State 2 Junior High School of Sorkam at the even semester of the 2016/2017 Academic Year. The sample of this study was class VIIIA as the experimental class and VIIIB as the control class. From the research data obtained a regression equation Y = 74,857 + 8.857X (there is a positive effect). The average value of students' understanding of mathematical concepts learned by the STAD cooperative learning model is 83,714, while the conventional learning model is 74,857. The coefficient of determination is 21.6%, meaning that 21.6% of the influence of the STAD type cooperative learning model on the ability to understand students' mathematical concepts. The results of the analysis of student responses were obtained (1) by 98.2% stating they were interested and the rest not; (2) amounting to 95.05% stating that there are benefits obtained and the rest not; (3) amounting to 86.78% stated that there were no obstacles experienced during the learning process and the rest stated there were; (4) 94.04% hoped the STAD type cooperative learning model was used in the learning process and the rest did not expect. So, it can be concluded that the student response is very positive because the average percentage of student approval responses to the STAD type cooperative learning model is â‰¥ 85%.